Reforming Ukraine's Pre-Trial Custody Measures: An International Law Perspective - Ganna Sobko; Andrii Svintsytskyi; Oleh Pushkar; Volodymyr Butynskyi; Yuliya Shvets (Khazanah Hukum, 2025)
This study examines how Ukraine's pre-trial custody measures can align with European Union standards, with a particular focus on addressing drug trafficking cases. By analysing theoretical, legislative, and practical aspects of pre-trial custody in serious and extremely serious drug-related crimes, the article identifies gaps in the Criminal Procedure Code of Ukraine and proposes specific reforms. The research emphasizes the international law perspective, referencing EU legal frameworks such as the European Convention on Human Rights and United Nations guidelines on pre-trial detention. Through an analysis of patterns in applying preventive measures and their impact on human rights, the study highlights the need for reforms that balance public safety and individual freedoms. Proposed reforms, including clearer criteria for applying custody, stricter regulations on alternative measures, and enhanced procedural safeguards, aim to ensure compliance with EU human rights standards while maintaining public safety. These changes are expected to improve procedural fairness, reduce arbitrariness in detention practices, and foster greater trust in Ukraine's judicial system. By addressing these issues, the reforms not only strengthen the rule of law domestically but also accelerate Ukraine’s integration into the European legal and governance framework.